Sinergi Mahasiswa dan Masyarakat untuk Dusun Ngemplak yang Berdaya - Muhajir, Mohamad; Firmansyah, Edoardo; Mustalifah, Cholif; Ahmadi, Ananda Putri; Rahayu, Mahmudah Rio; Khoirafi, Muhammad Nabil; Arifah, Sifa; Zaid, Galang Muhammad; Aulia, Nada Nadiah; Adianto, Randa; Alfitriyo, Age Agro (Universitas Muhammadiyah Yogyakarta, 2025)
Community Service of Universitas Muhammadiyah Yogyakarta in Dusun Ngemplak, Donokerto Village, Turi District, Sleman Regency, Special Region of Yogyakarta, has been successfully implemented. This initiative aimed to empower the local community through collaboration between university students and village residents. Various programs designed and carried out by the service team have produced positive impacts, including: (1) Improved children's ability to read the Qur'an and understand Islamic values through the Qur'anic Education Center (TPA); (2) Increased awareness among teenagers and mothers about the importance of reproductive health and balanced nutrition through educational sessions; (3) Regional mapping that resulted in a comprehensive village map to support better planning and management of village resources. In addition, other programs such as land management, communal work (gotong royong), exercise sessions, and administrative assistance for Posyandu (integrated health service post) and the PKK (Family Welfare Movement) have also successfully enhanced community participation in maintaining environmental cleanliness, promoting healthy lifestyles, and supporting a more organized village administration system. Overall, the collaboration between students and local residents has fostered a strong synergy in the effort to sustainably empower the community